Adolescent Emotions : Development, Morality, and Adaptation, YD. - Malti, Tina (J-B MHS Single Issue Mental Health Services., 2013)
Take an in depth look at how emotions relate to adolescents' decision making, reasoning, and behavior in morally relevant situations. It provides a summary of current research on emotions, morality, and adaptive behaviors. Furthermore, it discusses new approaches to research on emotions, morality, and socially adaptive behavior in adolescence. By doing so, the articles provide new insights into adolescents' emotional and moral development and show how emotions contribute to the way adolescents negotiate, resolve, and adapt to the moral and social conflicts that inevitably occur in their everyday lives.